Postoperative results and the effects of extended partial laryngectomy on the quality of life - Çıkrıkcı, Sercan; Gönüldaş, Burhanettin; Tunç, Orhan; Kanlıkama, Muzaffer (Journal of Surgery and Medicine, 2021)
Background/Aim: Larynx cancers account for 2-5% of all malignancies worldwide. With early diagnosis, radiotherapy or a partial laryngectomy may help preserve voice and laryngeal functions and reduce morbidity. This study aimed to evaluate how laryngeal functions, voice, and life quality were affected in larynx cancer patients after partial and extended partial laryngectomy. Methods: The patients who were diagnosed with larynx cancer and underwent partial (supraglottic laryngectomy (SGL), supracricoid laryngectomy (SCL)) or extended partial laryngectomy (extended supraglottic laryngectomy (ESGL) and extended supracricoid laryngectomy (ESCL)) between May 2010 and December 2015 in the otorhinolaryngology clinic of a Training and Research Hospital were included in this study. A questionnaire comprising three forms was filled in by these patients. Voice quality, duration of hospitalization, time until removal of the nasogastric tube, location of the tumor, time of decannulation, swallowing, and cough were compared with regards to the types of laryngectomies. Results: Our study began with 102 patients who had a partial laryngectomy; however, twelve who eventually had to undergo a total laryngectomy were excluded. Of the remaining 90 patients, 67 filled out our questionnaire. Functional score (FS), social functional score (SFS), symptom score (SS), fatigue score (FAS), general health score (GHS), and swallowing symptoms score (HNSW) were calculated and compared. These scores did not differ with the types of laryngectomies. In terms of voice quality, there were significant differences between ESCL-SGL, SCL-SGL, ESGL-SGL groups (P=0.001, P=0.004, and P=0.004, respectively). Conclusion: Despite numerous changes in swallowing physiology and larynx anatomy after partial and extended partial laryngectomy, swallowing function is restored, and the patients can lead a healthy life.